Novel multimeric IL-1 receptor antagonist for the treatment of rheumatoid arthritis. (February 2015) - Pasi, Shweta; Kant, Ravi; Gupta, Sarika; Surolia, Avadhesha
Abstract: Protein therapeutics targeting inflammatory mediators have shown great promise for the treatment of autoimmunities such as rheumatoid arthritis (RA). However, a significant challenge in this area has been their low in vivo stability and consequently their severely compromised therapeutic efficacy. One such therapeutic molecule IL-1 receptor antagonist (IL-1ra), used in the treatment of rheumatoid arthritis, has displayed only modest efficacy in human clinical trials owing to its short biological half-life. Herein, we report a novel approach to conglomerate individual protein entities into a drug depot by incorporation of an amyloidogenic motif Lys-Phe-Phe-Glu (KFFE) thereby dramatically improving their systemic persistence and in turn their therapeutic efficacy in a mice model of autoimmune arthritis.